2008
DOI: 10.2217/14796694.4.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology of the Wild and Mutant Brca1 Gene and Types of Hormonal Carcinogenesis

Abstract: Information related to the BRCA1 gene has increasingly become a subject for analysis by endocrinologists. For example, it is hard to dismiss the fact that, in BRCA1 mutation carriers, tumors develop predominantly in such estrogen-dependent organs as the mammary glands and ovaries but not in the endometrium. Another characteristic feature is that although BRCA1 mutants and knock-downs are unable to inhibit the transcriptional activity of estrogen receptor-alpha, in BRCA1 mutation carriers breast cancers are oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 89 publications
0
19
0
3
Order By: Relevance
“…The role of estrogen metabolites in BRCA1/2 -related breast carcinogenesis is complex and has not been well described [25, 26]. Estrogen receptor (ER)-α has been reported to activate BRCA1 expression within the breast and to provide protection against DNA damage and genome instability in ER-α positive breast cells.…”
Section: Introductionmentioning
confidence: 99%
“…The role of estrogen metabolites in BRCA1/2 -related breast carcinogenesis is complex and has not been well described [25, 26]. Estrogen receptor (ER)-α has been reported to activate BRCA1 expression within the breast and to provide protection against DNA damage and genome instability in ER-α positive breast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, BRCA1 gene mutation carriership even in breast cancer patients without verifi ed active tumor tissue was associated with signs of hyperestrogenemia and progenotoxic shift in the estrogen (4OHE1) and glucose systems (predominance of glucose-induced production of ROS over C-peptidemia/ insulinemia), which could have an unfavorable impact for the disease course and required correction. Treatment of this kind in breast cancer patients with BRCA1 gene mutations may include, with consideration for available data, aromatase inhibitors, biguanides (metformin), and antigenotoxicants (N-acetylcystein) [4,7,10], though it is obvious that the search for means useful in this respect should be continued. Note.…”
Section: Resultsmentioning
confidence: 99%
“…This interest, along with predominant receptor-negative phenotype of breast tumors in BRCA1+ cases [8], is explained, among other things, by possible role of hormonal support of realization of the genetic liability to malignant tumors. One more aspect of the problem is possible role of the mutant BRCA1 gene and its products as potential modulators of the endocrine genotoxic switch-over towards more intensive DNA-damaging effects of hormones and hormone-associated metabolites [1,4].…”
mentioning
confidence: 99%
“…Additionally, other studies demonstrated that estrogen deficiency in ovariectomized rats is followed by reduced UCP1 expression [25] while other studies have demonstrated that IGF-1 can induce UCP-1 expression in vitr o and in vivo models [26,27]. Indeed, several lines of evidence have demonstrated that both experimental mouse models and humans that are deficient in BRCA1 have abnormally high levels of estrogen/IGF-1 signaling and production [28-33]. In particular, experimental and epidemiological studies have demonstrated that loss of BRCA1 function can lead to the loss of the normal restraint on estrogen receptor signaling [34-36] and also an increase in estrogen production through increased expression of aromatase, an enzyme responsible for a key step in the biosynthesis of estrogens [37].…”
Section: Discussionmentioning
confidence: 99%